Disabled Students in Welsh Higher Education A Framework for Equality and Inclusion - Beauchamp-Pryor, Karen; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
The book provides an understanding of why disabled students experience inequality and exclusion within higher education and identifies those areas where change is needed to secure an inclusive educational environment.
Keywords: Education; Education; Education (general).